Direct Closure Technique for Superior Palpebra Defect in Sebaceous Gland Carcinoma Palpebra - Mandela, Kelvin; Mardijas Efendi; Hendriati (HM Publisher, 2023)
Background: Sebaceous Gland Carcinoma (SGC) palpebra is a malignancy tumor on the palpebra that originates from the sebaceous gland. These tumors can spread peripherally through intraepithelial or pagetoid growths. The main management is surgery, and the defect reconstruction is performed according to the size and area of the defect. Case presentation: A 53-year-old female patient came with a mass on the upper eyelid of the right eye for 1 year, which progressively grew in size and stuck to the eyelid, with no bleeding and no pain. The history of treatment has not provided an adequate response for the last 1 year. Visual acuity was 6/12 in both eyes, and a mass was found approximately 8x8 mm in size, nodular, fixed, and accompanied by madarosis. The histopathological examination showed a palpebral sebaceous gland carcinoma. There was no enlargement of submandibular or parotid lymph nodes. The patient underwent a wide excision of the upper eyelid lesion. Then, the defect was reconstructed by direct closure technique. The patient has been controlled 4 weeks of follow‑up. The functional and cosmetic outcomes were satisfied. Conclusion: After a month of follow-up, no recurrence occurred. Reconstruction with direct closure technique has good results in terms of anatomy, function, and cosmetics.